The potential for sustainable drainage systems (SuDS) in a regional urbanization project - Chapman, Cherona; Hall, Jim W. (Frontiers in Sustainable Cities, 2022)
With global urban populations expected to reach 5 billion by 2030, large-scale urban development is required to support and sustain this growing populous. At the same time, city planners are facing the pressures of climatic changes, which forecast more intense rainfall events, further exacerbating the existing challenge of surface water flooding in urban locations. Sustainable drainage systems (SuDS) are one proposed solution to help alleviate such problems, yet much still remains to be known about their operation, performance and potential benefit provision beyond the neighbourhood scale, or within a mixed-form development. Using a case study of the Cambridge to Oxford Arc (a region of England earmarked for extensive urbanisation), development patterns of different extents and spatial layout were modelled. The Stormwater Management Model (SWMM) was then used to simulate surface water runoff conditions in these developments during a 1-in-10-year rainfall event. Whilst denser scenarios typically led to greater peak runoff rates and total runoff volumes, this was not always the case under some SuDS designs as the denser scenarios provided the opportunity for more SuDS provision. The proportion of different surface cover types had a strong influence of runoff volumes and rates (due to the different impermeable surface areas and SuDS provision), and since the different housing typologies offered different proportions under each development scenario, there was no single typology that showed the lowest or highest runoff volume across all scenarios. The findings of this study highlight the importance in a planning context of considering multiple typologies and their footprints of different surfaces to maximise the potential of the development design in achieving the development’s goals.